Positive electrode active material and preparation method thereof, battery monomer and electric device

By using lithium-containing phosphate positive electrode active material in the battery to control its structure and carbon cladding, the long cycle life and high energy density of the battery are achieved, and the problem of short battery life is solved.

CN119275251AActive Publication Date: 2025-01-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310833253.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

The existing batteries have a short lifespan during circulation, making it difficult to take into account long cycle life, high energy density and good kinetic performance.

Method used

Lithium-containing phosphate is used as the positive electrode active material. By having (311) and (011) crystal surface peaks in a fully charged state, and controlling the content and specific surface area of ​​the carbon cladding layer are formed to form a single crystal structure to achieve a slowdown of some lithium. release.

Benefits of technology

It significantly extends the cycle life of the battery, improves energy density and kinetic performance, and reduces the problems of super stickiness of the slurry and coating cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275251A_ABST
    Figure CN119275251A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode active material and a preparation method thereof, a battery monomer and a power utilization device, the positive electrode active material comprises lithium-containing phosphate, and an X-ray diffraction pattern of the positive electrode active material in a full charge state satisfies the following conditions: the positive electrode active material has a (311) crystal face peak in a range of 35-36 degrees, has a (011) crystal face peak in a range of 20-21 degrees, and has a (011) crystal face peak in a range of 0-30 degrees. And the ratio of the peak intensity I311 of the (311) crystal face peak to the peak intensity I011 of the (011) crystal face peak satisfies I311 / I011 > = 0.008. The positive electrode active material provided by the invention can improve the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a positive electrode active material and a preparation method thereof, a battery cell and an electrical device. Background Art

[0002] In recent years, batteries have been widely used in energy storage power stations, for example, the demand for peak-valley regulation of power grids has increased. As a result, the requirements for the cycle life of batteries for energy storage have become increasingly higher. However, how to make batteries have a longer cycle life is still a difficulty in current battery development. Summary of the invention

[0003] The present application provides a positive electrode active material and a preparation method thereof, a battery cell and an electrical device, which can improve the cycle performance of the battery.

[0004] In a first aspect, the present application provides a positive electrode active material, the positive electrode active material comprising a lithium-containing phosphate, and the X-ray diffraction spectrum of the positive electrode active material tested in a fully charged state satisfies: having a (311) crystal plane peak in the range of 35°-36°, having a (011) crystal plane peak in the range of 20°-21°, and a peak intensity I of the (311) crystal plane peak 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.008.

[0005] The positive electrode active material provided in the present application has a portion of lithium-containing phosphate that has not been de-lithiated in the initial fully charged state. The portion of lithium-containing phosphate that has not been de-lithiated can be gradually activated during the battery cycle process, and the active lithium can be gradually released. Therefore, the positive electrode active material provided in the present application can play the role of a capacity sustained release agent, so that the battery using it can have a long cycle life.

[0006] In any embodiment, 0.009≤I 311 / I 011 ≤0.037, optionally, 0.012≤I 311 / I 011 ≤0.024. This allows the battery to have long cycle life, high energy density and good kinetic performance.

[0007] In any embodiment, the lithium-containing phosphate has a carbon coating layer on at least a portion of its surface.

[0008] In any embodiment, the weight content of the carbon coating layer is recorded as m, based on the total weight of the positive electrode active material, the specific surface area of ​​the positive electrode active material is recorded as A, and the unit is m 2 / g, 5.0≤A / (100×m)≤9.0, optionally, 6.4≤A / (100×m)≤8.2. This allows the battery to better combine long cycle life, high energy density and good kinetic performance.

[0009] In any embodiment, 1.0%≤m≤3.4%, optionally, 1.2%≤m≤2.0%. When the weight content m of the carbon coating layer is within the above range, the lithium phosphate body can be better coated, and the lithium phosphate body can be over-coated, thereby partially hiding the initial capacity of the positive electrode active material, and the positive electrode active material can play the role of a capacity sustained release agent.

[0010] In any embodiment, A≤18.5m 2 / g, optionally, A≤13.5m 2 When the specific surface area of ​​the positive electrode active material is within the above range, the processing performance of the positive electrode slurry and the positive electrode sheet can be improved, and the problems of excessive slurry stickiness and coating cracking can be reduced.

[0011] In any embodiment, the positive electrode active material is a single crystal structure or a quasi-single crystal structure.

[0012] In any embodiment, the volume distribution particle size Dv50 of the positive electrode active material is 0.6 μm-2.5 μm, and can be optionally 0.7 μm-2.3 μm. When the volume distribution particle size Dv50 of the positive electrode active material is within the above range, the positive electrode active material can have good ion transport performance, so that the battery can have good power performance, and the processing performance of the positive electrode slurry and the positive electrode sheet can be improved, for example, the problem of slurry super stickiness and coating cracking can be reduced.

[0013] In any embodiment, the powder resistivity of the positive electrode active material at 25° C. is recorded as δ, δ≤20Ω.cm, and optionally, δ≤12.1Ω.cm. When the powder resistivity of the positive electrode active material is within the above range, the electronic conductivity of the lithium-containing phosphate can be improved, and the hydrophilicity of the lithium-containing phosphate can be reduced, and the adsorption of water can be reduced, thereby further improving the cycle performance of the battery.

[0014] In any embodiment, the lithium-containing phosphate includes one or more of lithium iron phosphate and its doped and modified compounds. Optionally, the lithium-containing phosphate includes a molecular formula of Li m A x Fe 1-y B y P 1-z C z O 4-n D nA comprises one or more elements selected from Zn, Al, Na, K, and Mg; B comprises one or more elements selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, and Ti; C comprises one or more elements selected from B, S, Si, and N; D comprises one or more elements selected from S, F, Cl, and Br; m is selected from the range of 0.5 to 1.15, and can be selected from the range of 0.95 to 1.05; x is selected from the range of 0 to 0.1, and can be selected from the range of 0.001 to 0.005; y is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1; z is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1; n is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1.

[0015] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising the following steps: providing a lithium-containing phosphate precursor; grinding the lithium-containing phosphate precursor and a carbon source; heating the ground material to a first temperature T1 at a first rate under a protective gas atmosphere and keeping it at the first temperature T1 for a first time t1, and then heating it to a second temperature T2 at a second rate and keeping it at the second temperature T2 for a second time t2, to obtain a positive electrode active material, wherein the positive electrode active material includes a lithium-containing phosphate, and the X-ray diffraction spectrum of the positive electrode active material tested in a fully charged state satisfies: having a (311) crystal plane peak in the range of 35°-36°, having a (011) crystal plane peak in the range of 20°-21°, and the peak intensity I of the (311) crystal plane peak is 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.008.

[0016] In any embodiment, the first rate is less than or equal to 4°C / min, and can be selected from 1°C / min to 4°C / min. This not only allows the positive electrode active material to act as a capacity sustained release agent, but also allows the positive electrode active material particles to have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), so that the positive electrode active material can have good kinetic properties, and thus the battery using the positive electrode active material can have a long cycle life, good kinetic properties and high energy conversion efficiency.

[0017] In any embodiment, the first temperature T1 is greater than or equal to 400° C., and may be 400° C.-600° C., and may be 450° C.-550° C. By adjusting the first temperature T1 within the above range, the carbon source can be fully decomposed to form carbon, and the positive electrode active material particles can have uniform primary particle (herein, the primary particles are primary particles of single crystal particles) size, so that the positive electrode active material can better play the role of a capacity sustained release agent, and thus the battery using the positive electrode active material can have a long cycle life.

[0018] In any embodiment, the first time t1 is greater than or equal to 1 hour, and may be 1 hour to 7 hours, and may be 3 hours to 5 hours. This not only allows the positive electrode active material to act as a capacity sustained release agent, but also allows the positive electrode active material particles to have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), thereby allowing the positive electrode active material to have good kinetic properties, and thus the battery using the positive electrode active material can have a long cycle life, good kinetic properties and high energy conversion efficiency.

[0019] In any embodiment, the second temperature T2 is greater than or equal to 720°C, and may be 720°C-850°C, and may be 750°C-810°C. This allows the positive electrode active material particles to have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), which can not only make the positive electrode active material have good kinetic properties, but also make the positive electrode active material act as a capacity sustained release agent, and thus make the battery using the positive electrode active material have a long cycle life, good kinetic properties and high energy conversion efficiency.

[0020] In any embodiment, the second rate is 1°C / min-10°C / min, and can be 5°C / min-9°C / min. This allows the positive electrode active material particles to have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), which can not only make the positive electrode active material have good kinetic properties, but also make the positive electrode active material act as a capacity slow release agent.

[0021] In any embodiment, the second time t2 is 5h-20h, and can be 8h-15h. This allows the positive electrode active material particles to have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), which can not only make the positive electrode active material have good kinetic properties, but also make the positive electrode active material act as a capacity slow-release agent.

[0022] In any embodiment, the carbon source includes a first carbon source, and the first carbon source includes a water-soluble polymer. When the first carbon source includes a water-soluble polymer, the water-soluble polymer can fully wrap the lithium-containing phosphate precursor, thereby making the formed carbon coating layer more uniform and dense, thereby helping to hide part of the initial capacity of the positive electrode active material, so that the positive electrode active material can play the role of a capacity sustained release agent.

[0023] In any embodiment, the weight content of the first carbon source is ≥50%, optionally 50%-70%, based on the total weight of the carbon source, thereby facilitating the battery to have a long cycle life, high energy density and good kinetic performance.

[0024] In any embodiment, the water-soluble polymer includes one or more of polyethylene glycol, polyaniline, and their respective derivatives. When the water-soluble polymer is within the above range, the electronic conductivity of the lithium-containing phosphate can be improved, and the specific surface area of ​​the prepared positive electrode active material can be reduced, so that the formed carbon coating layer can be more uniform and dense, which helps to hide part of the initial capacity of the positive electrode active material, so that the positive electrode active material can play the role of a capacity sustained release agent.

[0025] In any embodiment, the carbon source further comprises a second carbon source, wherein the second carbon source comprises one or more of glucose, sucrose, lactose, and maltose.

[0026] In any embodiment, the weight content of the second carbon source is ≤50%, and can be 30%-50%, based on the total weight of the carbon source. This is beneficial for the battery to have a long cycle life, high energy density and good kinetic performance, and is also beneficial for reducing the raw material cost of the battery.

[0027] The third aspect of the present application provides a battery cell, including a positive electrode plate, the positive electrode plate including a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer including the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the preparation method of the second aspect of the present application.

[0028] A fourth aspect of the present application provides an electrical device comprising the battery cell of the third aspect of the present application.

[0029] The electric device of the present application includes the battery cell provided by the present application, and thus has at least the same advantages as the battery cell provided by the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some implementation methods of the present application, and for ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.

[0031] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.

[0032] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.

[0033] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.

[0034] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.

[0035] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.

[0036] Figure 6 It is a schematic diagram of an embodiment of an electrical device including the battery of the present application as a power source.

[0037] Figure 7 This is the X-ray diffraction pattern of the positive electrode sheet obtained by disassembling the battery prepared in Example 5 after full charging.

[0038] In the drawings, the drawings may not be drawn according to the actual scale. The reference numerals are as follows: 1 battery pack, 2 upper box, 3 lower box, 4 battery module, 5 battery cell, 51 housing, 52 electrode assembly, 53 cover plate. DETAILED DESCRIPTION

[0039] Hereinafter, the embodiments of the positive electrode active material and preparation method thereof, battery cell and electric device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0040] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0041] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0042] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0043] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] If not otherwise specified, in this application, the terms "first", "second", etc. are used to distinguish different objects rather than to describe a specific order or a primary-secondary relationship.

[0045] In the present application, the terms "plurality" and "multiple" refer to two or more.

[0046] In the description of the embodiments of the present application, unless otherwise specified, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Furthermore, a first feature being “above”, “above”, or “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, or “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0047] Unless otherwise specified, the terms used in this application have the commonly understood meanings that are commonly understood by those skilled in the art.

[0048] Unless otherwise specified, the values ​​of the parameters mentioned in this application can be measured by various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application. Unless otherwise specified, the test temperature of each parameter is 25°C.

[0049] The battery mentioned in the embodiments of the present application may be a single physical module including one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in the present application may include a battery cell, a battery module or a battery pack.

[0050] A battery cell is the smallest unit of a battery, which can independently realize the functions of charging and discharging. The battery cell can be cylindrical, rectangular or in other shapes, etc., which is not limited in the embodiments of the present application. Figure 1 The battery cell 5 is a rectangular parallelepiped structure as an example.

[0051] When there are multiple battery cells, the multiple battery cells are connected in series, in parallel, or in mixed connection through a busbar. In some embodiments, the battery may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module. In some embodiments, the battery may be a battery pack, which includes a case and battery cells, and the battery cells or battery modules are accommodated in the case. In some embodiments, the case may serve as part of the chassis structure of the vehicle. For example, part of the case may become at least a part of the floor of the vehicle, or part of the case may become at least a part of the crossbeam and longitudinal beam of the vehicle.

[0052] In some embodiments, the battery may be an energy storage device, which includes an energy storage container, an energy storage cabinet, and the like.

[0053] A battery cell generally includes an electrode assembly. The electrode assembly generally includes a positive electrode sheet and a negative electrode sheet. The electrode assembly may be a wound structure or a laminated structure, which is not limited in the present application.

[0054] The battery cell may also include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte. The outer package may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).

[0055] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to needs.

[0056] In some embodiments, battery cells may be assembled into a battery module. The battery module may contain multiple battery cells, and the specific number may be adjusted according to the application and capacity of the battery module. Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.

[0057] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.

[0058] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0059] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a box body and a plurality of battery modules 4 disposed in the box body. The box body includes an upper box body 2 and a lower box body 3, and the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the box body in any manner.

[0060] In order to improve the cycle life of batteries, the commonly used strategy is to replenish lithium. However, the large-scale industrialization of lithium replenishment technology still requires technological progress, and whether it is positive or negative electrode lithium replenishment, the utilization rate of lithium is low, and it will also increase costs.

[0061] Another common strategy is to add some additives to the electrolyte. The principle of the additives is usually to form a dense SEI film at the negative electrode or a dense CEI film at the positive electrode. However, this usually deteriorates the kinetic performance of the battery, thereby reducing the energy conversion efficiency, and the improvement of the battery cycle life is also limited.

[0062] In view of this, the inventors propose a novel positive electrode active material, which can enable a battery using the same to have a long cycle life.

[0063] The positive electrode active material provided in the embodiment of the present application includes a lithium-containing phosphate, and the X-ray diffraction spectrum of the positive electrode active material tested in a fully charged state satisfies: having a (311) crystal plane peak in the range of 35°-36°, having a (011) crystal plane peak in the range of 20°-21°, and the peak intensity I of the (311) crystal plane peak 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.008.

[0064] The X-ray diffraction pattern of the positive electrode active material tested in a fully charged state can be obtained by fully charging a battery containing the positive electrode active material, then disassembling the positive electrode sheet from the fully charged battery and testing it using an X-ray diffractometer.

[0065] The positive electrode active material being in a fully charged state corresponds to a battery containing the positive electrode active material being in a fully charged state, while the positive electrode active material itself is in a delithiated state.

[0066] In X-ray diffraction analysis, a copper target can be used as the anode target, and CuKα rays can be used as the radiation source. The scanning 2θ angle range may be 15°-45°, and the scanning rate may be 2° / min.

[0067] The (311) crystal plane peak represents the diffraction peak of the lithium-containing phosphate that has not been delithiated, and the (011) crystal plane peak represents the diffraction peak of the lithium-containing phosphate that has been delithiated. The peak intensity of the (311) crystal plane peak is 311 The peak intensity of the (011) crystal plane peak I 011 The ratio can be adopted as the ratio of the peak height of the (311) crystal plane peak to the peak height of the (011) crystal plane peak.

[0068] When the positive electrode active material (i.e., the battery containing the positive electrode active material) is fully charged, it can be charged at a constant current of 1C to the upper cut-off voltage of the battery, and then charged at a constant voltage to a current of 0.05C. The test temperature is 25°C. When the positive electrode active material is lithium iron phosphate (LiFePO4) and its doped and modified compounds, the upper cut-off voltage can be 3.65V.

[0069] The X-ray diffraction spectrum of the positive electrode active material provided in the embodiment of the present application tested in a fully charged state has a (311) crystal plane peak and a (011) crystal plane peak, and the peak intensity I of the (311) crystal plane peak is 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.008. This indicates that part of the lithium-containing phosphate in the positive electrode active material is not de-lithiated in the initial fully charged state, and the lithium-containing phosphate that is not de-lithiated can be gradually activated during the battery cycle, and the active lithium is gradually released. Therefore, the positive electrode active material provided in the embodiment of the present application can play the role of a capacity sustained release agent, so that the battery using it can have a long cycle life.

[0070] In some embodiments, 0.008≤I 311 / I 011 ≤0.037. 311 / I 011 When it is greater than 0.037, the positive electrode active material will have more lithium phosphates that are not de-lithiated in the initial fully charged state, that is, there is more initial capacity hidden, which is beneficial to improve the cycle life of the battery, but the initial capacity of the positive electrode active material will decrease, and the lithium ion transmission rate of the positive electrode active material will also decrease, which will also affect the energy density and kinetic performance of the battery. By further adjusting the peak intensity I of the (311) crystal plane peak 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies 0.008≤I 311 / I 011 ≤0.037, which is conducive to the battery having long cycle life, high energy density and good kinetic performance.

[0071] Optionally, 0.009≤I 311 / I 011 ≤0.037, 0.009≤I 311 / I 011 ≤0.034, 0.012≤I 311 / I 011 ≤0.024, 0.012≤I 311 / I 011 ≤0.022, 0.012≤I 311 / I011 ≤0.021, 0.013≤I 311 / I 011 ≤0.020, 0.013≤I 311 / I 011 ≤0.018. This allows the battery to have long cycle life, high energy density and good kinetic performance.

[0072] In some embodiments, the lithium-containing phosphate has a carbon coating on at least a portion of its surface.

[0073] In some embodiments, the weight content of the carbon coating layer is recorded as m, based on the total weight of the positive electrode active material, and the specific surface area of ​​the positive electrode active material is recorded as A, with a unit of m 2 / g, 5.0≤A / (100×m)≤9.0.

[0074] A / (100×m) has the following meaning: when the weight content m of the carbon coating layer is 1.0% and the specific surface area A of the positive electrode active material is 5m 2 / g, A / (100×m)=5÷(100×1.0%)=5.

[0075] The carbon coating layer in the positive electrode active material provided in the embodiment of the present application can provide a good conductive network, improve the electronic conductivity of the lithium phosphate, and can also play the role of over-coating the lithium phosphate body, thereby hiding part of the initial capacity of the positive electrode active material, and further making the positive electrode active material play the role of a capacity sustained release agent.

[0076] A / (100×m) can reflect the density of the carbon coating. When A / (100×m) is small, the kinetic performance of the positive electrode active material deteriorates and the internal resistance of the battery may be high; when A / (100×m) is large, the initial capacity of the positive electrode active material may be fully exerted at the initial full charge, which makes the positive electrode active material less effective as a capacity sustained release agent and is not good enough to improve the battery cycle performance. The inventors have found that by adjusting the weight content m of the carbon coating and the specific surface area A of the positive electrode active material to meet 5.0≤A / (100×m)≤9.0, the positive electrode active material can have a higher initial capacity and good kinetic performance, and can also better play the role of a capacity sustained release agent, so that the battery using the positive electrode active material can have a long cycle life, high energy density and good kinetic performance.

[0077] Optionally, 6.4≤A / (100×m)≤8.2, 7.1≤A / (100×m)≤8.2, 7.2≤A / (100×m)≤8.0. This allows the battery to better combine long cycle life, high energy density and good kinetic performance.

[0078] In some embodiments, the weight content m of the carbon coating layer satisfies 1.0%≤m≤3.4%, and optionally, 1.2%≤m≤2.0%. When the weight content m of the carbon coating layer is within the above range, the lithium-containing phosphate body can be better coated, and the lithium-containing phosphate body can be over-coated, thereby partially hiding the initial capacity of the positive electrode active material, and further allowing the positive electrode active material to act as a capacity slow-release agent.

[0079] The weight content m of the carbon coating layer can be tested by a carbon-sulfur analyzer, and the test standard can refer to GB / T20123-2006.

[0080] In some embodiments, the positive electrode active material has a single crystal structure or a quasi-single crystal structure.

[0081] In the present application, the term "single crystal-like" refers to particles formed by agglomeration of a small number of primary particles (eg, no more than 10 primary particles).

[0082] The carbon coating layer of the positive electrode active material with a quasi-single crystal structure includes both the carbon coating layer located on the outer surface of the entire lithium-containing phosphate and the carbon coating layer located on the surface of the primary particles constituting the quasi-single crystal particles. Therefore, the weight content m of the carbon coating layer refers to the total weight content of the carbon coating layers at different positions in the positive electrode active material.

[0083] In some embodiments, the specific surface area A of the positive electrode active material satisfies A≤18.5 m 2 / g, optionally, A≤13.5m 2 / g,5m 2 / g≤A≤13.5m 2 / g,7.6m 2 / g≤A≤13.5m 2 / g,8.8m 2 / g≤A≤13.5m 2 / g,9.0m 2 / g≤A≤13.1m 2 When the specific surface area of ​​the positive electrode active material is within the above range, the processing performance of the positive electrode slurry and the positive electrode sheet can be improved, and the problems of excessive slurry stickiness and coating cracking can be reduced.

[0084] The specific surface area of ​​the positive electrode active material is a well-known meaning in the art and can be measured using instruments and methods known in the art. For example, it can be measured by nitrogen adsorption specific surface area analysis test method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The test instrument can be the Tri-Star 3020 specific surface area pore size analysis tester from Micromeritics, USA.

[0085] In some embodiments, the volume distribution particle size Dv50 of the positive electrode active material may be 0.6 μm-2.5 μm, optionally 0.7 μm-2.3 μm, 1.0 μm-2.0 μm. When the volume distribution particle size Dv50 of the positive electrode active material is within the above range, the positive electrode active material can have good ion transport performance, thereby enabling the battery to have good power performance, and can also improve the processing performance of the positive electrode slurry and the positive electrode sheet, for example, it can reduce the problems of slurry super stickiness and coating cracking.

[0086] The Dv50 of the positive electrode active material is well known in the art and can be measured using instruments and methods known in the art. For example, it can be conveniently measured using a laser particle size analyzer (such as Malvern Mastersizer 3000) in accordance with GB / T 19077-2016. The physical definition of Dv50 is the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%.

[0087] In some embodiments, the powder resistivity of the positive electrode active material at 25°C is recorded as δ, δ≤20Ω.cm, optionally, δ≤12.1Ω.cm, 1.2Ω.cm≤δ≤12.1Ω.cm, 3.9Ω.cm≤δ≤12.1Ω.cm, 5.5Ω.cm≤δ≤11.1Ω.cm, 5.5Ω.cm≤δ≤10.0Ω.cm, 5.5Ω.cm≤δ≤9.1Ω.cm. When the powder resistivity of the positive electrode active material is within the above range, the electronic conductivity of the lithium-containing phosphate can be improved, and the hydrophilicity of the lithium-containing phosphate can be reduced, and the adsorption of water can be reduced, thereby further improving the cycle performance of the battery.

[0088] The powder resistivity of the positive electrode active material is well known in the art and can be measured using instruments and methods known in the art. For example, the test can be performed with reference to GB / T 32993-2016. The test temperature is 25°C.

[0089] In some embodiments, the lithium-containing phosphate may have an olivine structure.

[0090] In some embodiments, the lithium-containing phosphate includes one or more of lithium iron phosphate (LiFePO 4 ) and doping-modified compounds thereof.

[0091] In some embodiments, the lithium-containing phosphate may include a molecular formula of Li m A x Fe 1-y B y P 1-z C z O 4-n D nA comprises one or more elements selected from Zn, Al, Na, K, and Mg; B comprises one or more elements selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, and Ti; C comprises one or more elements selected from B, S, Si, and N; D comprises one or more elements selected from S, F, Cl, and Br; m is selected from the range of 0.5 to 1.15, and can be selected from the range of 0.95 to 1.05; x is selected from the range of 0 to 0.1, and can be selected from the range of 0.001 to 0.005; y is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1; z is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1; n is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1. The values ​​of m, x, y, z, and n need to keep the lithium-containing phosphate electrically neutral.

[0092] The battery is accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is usually different when the battery is discharged to different states. In the examples of the present application regarding the lithium-containing phosphate, the molar content of Li is the molar content of the lithium-containing phosphate in the initial state. When the positive electrode active material is used in the battery system, the molar content of Li usually changes after charge and discharge cycles.

[0093] [Preparation method]

[0094] The present application also provides a method for preparing the above positive electrode active material.

[0095] The method comprises the following steps: providing a lithium-containing phosphate precursor; grinding the lithium-containing phosphate precursor and a carbon source; heating the ground material to a first temperature T1 at a first rate under a protective gas atmosphere and keeping it at the first temperature T1 for a first time t1, and then heating it to a second temperature T2 at a second rate and keeping it at the second temperature T2 for a second time t2, to obtain a positive electrode active material. The positive electrode active material comprises a lithium-containing phosphate, and the X-ray diffraction spectrum of the positive electrode active material tested in a fully charged state satisfies: having a (311) crystal plane peak in the range of 35°-36°, having a (011) crystal plane peak in the range of 20°-21°, and the peak intensity I of the (311) crystal plane peak is 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.008.

[0096] In some embodiments, the first rate is less than or equal to 4°C / min. By adjusting the first rate within the above range, a dense and uniform carbon coating layer can be formed, thereby hiding part of the initial capacity of the positive electrode active material, making the positive electrode active material act as a capacity slow-release agent, and thus making the battery using the positive electrode active material have a long cycle life.

[0097] When the first rate is greater than 4°C / min, the compactness and uniformity of the carbon coating are poor, which results in sufficient contact between the lithium-containing phosphate and the electrolyte in the initial state. At this time, the X-ray diffraction spectrum of the positive electrode active material tested in the fully charged state does not have a (311) crystal plane peak in the range of 35°-36°, and the initial capacity of the positive electrode active material can be fully utilized. Therefore, it is difficult for the positive electrode active material to play the role of a capacity sustained release agent, and it is difficult for the battery using the positive electrode active material to have a long cycle life.

[0098] In some embodiments, the first rate may be 1°C / min-4°C / min, and may be 1.5°C / min-3.5°C / min, 1.5°C / min-3°C / min, or 1.5°C / min-2.5°C / min. By further adjusting the first rate within the above range, not only can the positive electrode active material act as a capacity sustained release agent, but also the positive electrode active material particles can have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), so that the positive electrode active material can have good kinetic properties, and thus the battery using the positive electrode active material can have a long cycle life, good kinetic properties, and high energy conversion efficiency.

[0099] In some embodiments, the first temperature T1 is greater than or equal to 400° C. By adjusting the first temperature T1 within the above range, the carbon source can be fully decomposed to form carbon.

[0100] In some embodiments, the first temperature T1 may be 400° C.-600° C., and may be 450° C.-550° C. By adjusting the first temperature T1 within the above range, the carbon source can be fully decomposed to form carbon, and the positive electrode active material particles can have uniform primary particle (herein, the primary particles are primary particles of single crystal particles) size, so that the positive electrode active material can better play the role of a capacity sustained release agent, and thus the battery using the positive electrode active material can have a long cycle life.

[0101] In some embodiments, the first time t1 is greater than or equal to 1 hour. By adjusting the first time t1 within the above range, the positive electrode active material particles can have a suitable and uniform primary particle size (the primary particles here are primary particles of single crystal particles), thereby hiding part of the initial capacity of the positive electrode active material, so that the positive electrode active material can play the role of a capacity sustained release agent, and thus the battery using the positive electrode active material can have a long cycle life.

[0102] When the first time t1 is less than 1h or 0, the size of the primary particles forming the positive electrode active material particles is too small, which will make the initial capacity of the prepared positive electrode active material fully utilized, and the X-ray diffraction spectrum of the positive electrode active material tested in the fully charged state does not have a (311) crystal plane peak in the range of 35°-36°. Therefore, it is difficult for the positive electrode active material to play the role of a capacity sustained release agent, and it is difficult for the battery using the positive electrode active material to have a long cycle life.

[0103] In some embodiments, the first time t1 may be 1h-7h, and may be 3h-5h. By further adjusting the first time t1 within the above range, not only can the positive electrode active material act as a capacity sustained release agent, but also the positive electrode active material particles can have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), so that the positive electrode active material can have good kinetic properties, and thus the battery using the positive electrode active material can have a long cycle life, good kinetic properties and high energy conversion efficiency.

[0104] In some embodiments, the second temperature T2 is greater than or equal to 720° C. By adjusting the second temperature T2 within the above range, the positive electrode active material particles can have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), thereby hiding part of the initial capacity of the positive electrode active material, so that the positive electrode active material can play the role of a capacity sustained release agent, and thus the battery using the positive electrode active material can have a long cycle life.

[0105] When the second temperature T2 is less than 720°C, the size of the primary particles forming the positive electrode active material particles is too small, which will cause the initial capacity of the prepared positive electrode active material to be fully utilized, and the X-ray diffraction spectrum of the positive electrode active material tested in the fully charged state does not have a (311) crystal plane peak in the range of 35°-36°. Therefore, it is difficult for the positive electrode active material to play the role of a capacity sustained release agent, and it is difficult for the battery using the positive electrode active material to have a long cycle life. At the same time, when the second temperature T2 is less than 720°C, the graphitization degree of the carbon coating layer formed on the surface of the lithium-containing phosphate will be relatively small, and the electronic conductivity will be relatively poor, which will also reduce the kinetic performance and energy conversion efficiency of the positive electrode active material and the battery.

[0106] The second temperature T2 should not be too high. When the second temperature T2 is high, the primary particles (here the primary particles are single-crystal-like primary particles) of the positive electrode active material particles are larger in size, which will reduce the kinetic performance of the positive electrode active material and the battery. In some embodiments, the second temperature T2 can be 720°C-850°C, optionally 750°C-810°C. By further adjusting the second temperature T2 within the above range, the positive electrode active material particles can have a suitable primary particle (here the primary particle is a single-crystal-like primary particle) size, which can not only make the positive electrode active material have good kinetic performance, but also make the positive electrode active material have the effect of a capacity sustained release agent, thereby making the battery using the positive electrode active material have a long cycle life, good kinetic performance and high energy conversion efficiency.

[0107] In some embodiments, the second rate may be 1°C / min-10°C / min, and may be 5°C / min-9°C / min. This allows the positive electrode active material particles to have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), which can not only give the positive electrode active material good kinetic properties, but also allow the positive electrode active material to function as a capacity slow-release agent.

[0108] In some embodiments, the first rate may be 1° C. / min-4° C. / min, and the second rate may be 5° C. / min-9° C. / min.

[0109] In some embodiments, the second time t2 may be 5h-20h, and may be 8h-15h. This allows the positive electrode active material particles to have a suitable primary particle size (the primary particles here are primary particles of single crystal particles), which can not only make the positive electrode active material have good kinetic properties, but also make the positive electrode active material act as a capacity slow-release agent.

[0110] In some embodiments, the carbon source includes a first carbon source, and the first carbon source includes a water-soluble polymer. When the first carbon source includes a water-soluble polymer, the water-soluble polymer can fully wrap the lithium-containing phosphate precursor, thereby making the formed carbon coating layer more uniform and dense, thereby helping to hide part of the initial capacity of the positive electrode active material, so that the positive electrode active material can play the role of a capacity sustained release agent.

[0111] In some embodiments, the water-soluble polymer may include one or more of polyethylene glycol, polyaniline, and their respective derivatives. Derivatives generally refer to products derived from the substitution of hydrogen atoms or atomic groups in a compound by other atoms or atomic groups.

[0112] When the water-soluble polymer is within the above range, the electronic conductivity of the lithium phosphate can be improved, and the specific surface area of ​​the prepared positive electrode active material can be reduced, so that the formed carbon coating layer can be more uniform and dense, which in turn helps to hide part of the initial capacity of the positive electrode active material, so that the positive electrode active material can play the role of a capacity sustained release agent.

[0113] In some embodiments, the weight content of the first carbon source may be ≥50%, based on the total weight of the carbon source. When the weight content of the first carbon source is within the above range, the obtained carbon coating layer can be made more uniform and dense, thereby helping to hide part of the initial capacity of the positive electrode active material, so that the positive electrode active material can play the role of a capacity slow release agent.

[0114] When the weight content of the first carbon source is less than 50%, the compactness of the formed carbon coating layer is poor, which results in sufficient contact between the lithium-containing phosphate and the electrolyte in the initial state. At this time, the X-ray diffraction spectrum of the positive electrode active material tested in the fully charged state does not have a (311) crystal plane peak in the range of 35°-36°, and the initial capacity of the positive electrode active material can be fully utilized. Therefore, it is difficult for the positive electrode active material to play the role of a capacity sustained release agent, and it is difficult for the battery using the positive electrode active material to have a long cycle life.

[0115] In some embodiments, the weight content of the first carbon source can be 50%-70%, based on the total weight of the carbon source. When the weight content of the first carbon source is large, more initial capacity of the positive electrode active material will be hidden in the initial full charge state, thereby improving the cycle life of the battery, but the initial capacity of the positive electrode active material will decrease; at the same time, the lithium ion transmission rate of the positive electrode active material will also decrease, thereby affecting the energy density and kinetic performance of the battery. By further adjusting the weight content of the first carbon source within the above range, it is beneficial for the battery to have a long cycle life, high energy density and good kinetic performance.

[0116] In some embodiments, the carbon source may further include a second carbon source, and the second carbon source may include one or more of glucose, sucrose, lactose, and maltose.

[0117] In some embodiments, the weight content of the second carbon source may be ≤50%, optionally 30%-50%, based on the total weight of the carbon source.

[0118] By further adjusting the weight content of the second carbon source within the above range, the battery can have a long cycle life, high energy density and good kinetic performance, and can also help reduce the raw material cost of the battery.

[0119] The amount of carbon source added can be calculated based on the residual carbon value of the carbon source (corresponding to the weight of the carbon coating layer in the positive electrode active material). In some embodiments, the weight content m of the carbon coating layer (i.e., the weight content of the residual carbon of the carbon source) satisfies 1.0%≤m≤3.4%, optionally, 1.2%≤m≤2.0%.

[0120] In some embodiments, the precursor of the lithium phosphate can be a mixture of various raw materials required for preparing the lithium phosphate, for example, it can include a lithium source, a metal source (such as an iron source, etc.), a phosphorus source, and optionally various doping element (such as A, B, C, D) sources, etc.

[0121] The lithium source may include one or more of lithium hydroxide, lithium carbonate, lithium phosphate, lithium oxalate, and lithium acetate.

[0122] The metal source may include one or more of oxides, hydroxides, halides, phosphates, oxalates, sulfates, carbonates, and nitrates of the metal elements.

[0123] The phosphorus source may include one or more of phosphoric acid, diammonium phosphate, diammonium hydrogen phosphate, ammonium phosphate, and iron phosphate.

[0124] The doping element source may include various compounds containing the doping element.

[0125] In some embodiments, iron phosphate (FePO 4 ) may be used as the iron source and the phosphorus source.

[0126] In some embodiments, during the step of grinding the lithium-containing phosphate precursor and the carbon source, a solvent, such as a mixture of one or more of water, ethanol, and propanol, may be added.

[0127] In some embodiments, after grinding the lithium phosphate precursor and the carbon source, spray drying can be performed, and then the spray-dried powder can be heated to a first temperature T1 at a first rate and kept at the first temperature T1 for a first time t1, and then heated to a second temperature T2 at a second rate and kept at the second temperature T2 for a second time t2 to obtain a positive electrode active material.

[0128] In some embodiments, the shielding gas may include one or more of nitrogen, argon, and helium.

[0129] In some embodiments, the obtained positive electrode active material may be subjected to a crushing process, which may be a gas flow crushing process.

[0130] In some embodiments, the method comprises the following steps: providing a lithium-containing phosphate precursor; grinding the lithium-containing phosphate precursor with a carbon source, wherein the carbon source comprises a first carbon source, wherein the first carbon source comprises one or more of polyethylene glycol, polyaniline, and their respective derivatives, and the weight content of the first carbon source is ≥50%, based on the total weight of the carbon source; heating the ground material to 400°C-600°C at a rate of 1°C / min-4°C / min under a protective gas atmosphere and keeping it at this temperature for 1h-7h, then heating it to 720°C-850°C at a rate of 5°C / min-9°C / min and keeping it at this temperature for 5h-20h, to obtain a positive electrode active material. Thus, the battery using the positive electrode active material can have a long cycle life, good kinetic performance, high energy density, and high energy conversion efficiency.

[0131] The method provided in the embodiment of the present application can prepare the positive electrode active material provided in the embodiment of the present application. Other parameters of the prepared positive electrode active material can refer to the above positive electrode active material and will not be repeated here.

[0132] [Positive electrode]

[0133] The positive electrode sheet provided in the embodiment of the present application includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. The positive electrode film layer includes the positive electrode active material as described above or the positive electrode active material prepared by the method as described above.

[0134] The positive electrode current collector has two surfaces opposite to each other in the thickness direction thereof, and the positive electrode film layer is arranged on any one or both of the two opposite surfaces of the positive electrode current collector.

[0135] In some embodiments, the positive electrode film layer may also include other positive electrode active materials in addition to the above positive electrode active materials or the positive electrode active materials prepared by the above method, for example, it may also include lithium transition metal oxides, etc., which is not limited in the embodiments of the present application.

[0136] In some embodiments, the positive electrode film layer may further optionally include a positive electrode conductive agent. The present application has no particular restrictions on the type of the positive electrode conductive agent. In some embodiments, as an example, the positive electrode conductive agent may include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0137] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. The present application has no particular restrictions on the type of positive electrode binder. In some embodiments, as an example, the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin.

[0138] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).

[0139] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, positive electrode binder, positive electrode conductive agent, etc. in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.

[0140] [Negative electrode]

[0141] The battery cell includes a negative electrode plate.

[0142] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0143] The negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is arranged on any one or both of the two opposite surfaces of the negative electrode current collector.

[0144] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0145] In some embodiments, the negative electrode active material may adopt materials known in the art. As an example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0146] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. As an example, the binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0147] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0148] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC)).

[0149] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the negative electrode conductive agent, the negative electrode binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0150] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate may also include a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector; in some embodiments, the negative electrode plate may also include a protective layer covering the surface of the negative electrode film layer.

[0151] [Electrolytes]

[0152] The battery cell also includes an electrolyte. The electrolyte plays a role in conducting ions between the positive electrode plate and the negative electrode plate. The present application does not specifically limit the type of electrolyte, which can be selected according to needs. For example, the electrolyte may include one or more of a solid electrolyte, a gel electrolyte, and a liquid electrolyte (i.e., an electrolyte).

[0153] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0154] The type of electrolyte salt is not specifically limited and can be selected according to actual needs. In some embodiments, the electrolyte salt may include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP) One or more.

[0155] The type of solvent is not specifically limited and can be selected according to actual needs. In some embodiments, as an example, the solvent may include ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE) One or more.

[0156] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.

[0157] [Isolation film]

[0158] The battery cell may also include a separator. The separator may be disposed between the positive electrode sheet and the negative electrode sheet, and mainly serves to prevent internal short circuits. The present application has no particular restrictions on the type of separator, and any known porous structure membrane with good chemical stability and mechanical stability may be selected.

[0159] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and polyimide. The isolation membrane may be a single-layer film or a multi-layer composite film. When the isolation membrane is a multi-layer composite film, the materials of each layer are the same or different.

[0160] The preparation method of battery cells is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator, and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the above-mentioned electrolyte is injected after drying. After vacuum packaging, standing, formation and other processes, a battery cell is obtained. Multiple battery cells can also be further connected in series, in parallel or in mixed connection to form a battery module. Multiple battery modules can also be connected in series, in parallel or in mixed connection to form a battery pack. In some embodiments, multiple battery cells can also directly form a battery pack.

[0161] The present application also provides an electrical device, which includes a battery provided in the present application. The battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device can be, but is not limited to, a mobile device (such as a mobile phone, a tablet computer, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.

[0162] The electric device can select the type of battery according to its usage requirements, such as a battery cell, a battery module or a battery pack.

[0163] Figure 6 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module can be used.

[0164] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.

[0165] Example

[0166] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0167] Example 1

[0168] (1) Preparation of positive electrode active materials

[0169] FePO4, Li2CO3, glucose and polyethylene glycol are mixed evenly, a small amount of water is added, and the mixture is spray-dried after grinding; the spray-dried powder is placed in a sintering furnace, and the temperature is increased from 25°C to 500°C (first temperature T1) at a rate of 2°C / min (first rate) under a nitrogen atmosphere and kept at this temperature for 3 hours (first time t1), and then the temperature is increased to 780°C (second temperature T2) at a rate of 5°C / min (second rate) and kept at this temperature for 10 hours (second time t2), and then the temperature is lowered and crushed by air flow to obtain the positive electrode active material, i.e., carbon-coated LiFePO4.

[0170] The carbon source is a mixture of glucose and polyethylene glycol in a mass ratio of 5:5, and the amount of carbon source added is such that the weight content of the residual carbon of the carbon source (ie, the weight content m of the carbon coating layer) is 1.29%, based on the total weight of the prepared positive electrode active material.

[0171] (2) Preparation of batteries

[0172] The positive electrode active material, carbon black SP and polyvinylidene fluoride (PVDF) were uniformly mixed in an N-methylpyrrolidone solvent system at a weight ratio of 92:2.5:5.5, and then coated on an aluminum foil, dried and cold pressed to obtain a positive electrode sheet.

[0173] The negative electrode active materials graphite, acetylene black, styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) were mixed uniformly in deionized water at a weight ratio of 95:2:2:1, coated on a copper foil, dried, and cold pressed to obtain a negative electrode sheet.

[0174] Ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0175] Using a polyethylene (PE) porous polymer film as a separator, the positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrodes to play a role of isolation, and then wound to obtain an electrode assembly. The electrode assembly is placed in an outer package, injected with electrolyte and packaged, and after processes such as formation, a battery is obtained.

[0176] Examples 2-14 and Comparative Examples 1-5

[0177] The preparation method of the battery is similar to that of Example 1, except that the preparation parameters of the positive electrode active material are different, which are specifically shown in Table 1. In Table 1, m represents the weight content ratio of the carbon coating layer (residual carbon of the carbon source) based on the total weight of the prepared positive electrode active material; the first time t1 is 0, which means that the heat preservation is not performed at the first temperature.

[0178] Performance Testing

[0179] (1) X-ray diffraction analysis of positive electrode active materials

[0180] At 25°C, the battery prepared above was charged to 3.65V at 1C constant current, and then charged to 0.05C at constant voltage, at which time the battery was in a fully charged state; the positive electrode sheet was then disassembled from the fully charged battery and tested by an X-ray diffractometer. The positive electrode active material being in a fully charged state corresponds to the battery being in a fully charged state, while the positive electrode active material itself is in a delithiation state.

[0181] In the X-ray diffraction analysis test, a copper target is used as the anode target, and CuKα rays are used as the radiation source. The scanning 2θ angle range is 15°-45°, and the scanning rate is 2° / min. The testing instrument can be a Bruker D8 Discover X-ray diffraction analyzer.

[0182] In the obtained X-ray diffraction spectrum, there is a (311) crystal plane peak (LiFePO4 phase) in the range of 35°-36°, a (011) crystal plane peak (FePO4 phase) in the range of 20°-21°, I 311 / I 011 It represents the ratio of the peak height of the (311) crystal plane peak to the peak height of the (011) crystal plane peak.

[0183] (2) Battery cycle performance test

[0184] At 25°C, the prepared battery was left to stand for 30 minutes and then tested as follows. The battery was charged to 3.65V at a constant power of 0.5P; after standing for 10 minutes, the battery was discharged to 2.5V at a constant power of 0.5P. The above steps were repeated until the discharge capacity of the battery decayed to 90% of the discharge capacity of the first cycle of the battery, and the number of cycles of the battery was recorded.

[0185] (3) Initial DC internal resistance test of the battery

[0186] At 25°C, the battery prepared above is charged to 3.65V at 0.5C constant current, and then charged to 0.05C at constant voltage; the battery is discharged at 0.5C constant current for 60min to adjust the battery to 50% SOC, at which time the battery voltage is recorded as U1; the battery is discharged at 1C constant current for 30 seconds, with 0.1 second sampling, and the voltage at the end of discharge is recorded as U2. The discharge DCR of the battery at 50% SOC represents the initial DC internal resistance DCR of the battery, DCR = (U1-U2) / 1C.

[0187] Table 2 shows the test results of the above embodiments and comparative examples.

[0188] In Table 2, A represents the specific surface area of ​​the prepared positive electrode active material, in m 2 / g; δ represents the powder resistivity of the prepared positive electrode active material at 25°C, in Ω.cm. The specific surface area and powder resistivity of the positive electrode active material at 25°C can be tested according to the test method given in the specification.

[0189] Table 1

[0190]

[0191] Table 2

[0192]

[0193] From the test results of Table 1 and Table 2, it can be seen that the X-ray diffraction patterns of the positive electrode active materials prepared in Comparative Examples 1 to 5 tested in the fully charged state do not have a (311) crystal plane peak, and the positive electrode active materials do not have a capacity sustained release effect at this time, and the cycle life of the batteries using the positive electrode active materials is relatively short.

[0194] It can be seen from the test results of Table 1 and Table 2 that by adjusting the peak intensity I of the (311) crystal plane peak in the X-ray diffraction spectrum of the positive electrode active material tested in the fully charged state 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.008, which can make the battery have a long cycle life.

[0195] Figure 7 This is the X-ray diffraction pattern of the positive electrode sheet obtained by disassembling the battery prepared in Example 5 after full charge. Figure 7 It can be seen that the X-ray diffraction spectrum of the positive electrode active material tested in the fully charged state has a (311) crystal plane peak, and the peak intensity of the (311) crystal plane peak is 311The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.008, which indicates that part of the lithium iron phosphate in the prepared positive electrode active material has not been de-lithiated. The part of the lithium iron phosphate that has not been de-lithiated can be gradually activated during the battery cycle, and the active lithium can be gradually released, thereby making the positive electrode active material act as a capacity sustained release agent, and thus making the battery using it have a long cycle life.

[0196] It can be seen from the test results of Table 1 and Table 2 that by adjusting the peak intensity I of the (311) crystal plane peak in the X-ray diffraction spectrum of the positive electrode active material tested in the fully charged state 311 The peak intensity of the (011) crystal plane peak I 011 The ratio further satisfies 0.012≤I 311 / I 011 ≤0.024, which can also make the battery have a longer cycle life under the premise of lower internal resistance and good kinetic performance.

[0197] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material includes a lithium-containing phosphate, and the X-ray diffraction spectrum of the positive electrode active material tested in a fully charged state satisfies: having a (311) crystal plane peak in the range of 35°-36°, having a (011) crystal plane peak in the range of 20°-21°, and a peak intensity I of the (311) crystal plane peak 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.

008.

2. The positive electrode active material according to claim 1, characterized in that 0.009 ≤ I 311 / I 011 ≤0.037, selectable area, 0.012≤I 311 / I 011 ≤0.

024.

3. The positive electrode active material according to any one of claims 1 to 2, characterized in that: The lithium-containing phosphate has a carbon coating layer on at least a portion of its surface; Optionally, the weight content of the carbon coating layer is recorded as m, based on the total weight of the positive electrode active material, the specific surface area of ​​the positive electrode active material is recorded as A, with a unit of m 2 / g, 5.0≤A / (100×m)≤9.0, more preferably, 6.4≤A / (100×m)≤8.

2.

4. The positive electrode active material according to claim 3, characterized in that 1.0%≤m≤3.4%, optionally, 1.2%≤m≤2.0%; and / or, A≤18.5m 2 / g, optionally, A≤13.5m 2 / g.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The positive electrode active material is a single crystal structure or a quasi-single crystal structure.

6. The positive electrode active material according to any one of claims 1 to 5, characterized in that: The volume distribution particle size Dv50 of the positive electrode active material is 0.6 μm-2.5 μm, and can be 0.7 μm-2.3 μm; and / or, The powder resistivity of the positive electrode active material at 25° C. is denoted as δ, δ≤20Ω.cm, and optionally, δ≤12.1Ω.cm.

7. The positive electrode active material according to any one of claims 1 to 6, characterized in that: The lithium-containing phosphate includes one or more of lithium iron phosphate and its doped and modified compounds; Optionally, the lithium-containing phosphate includes a molecular formula of Li m A x Fe 1-y B y P 1-z C z O 4-n D n A comprises one or more elements selected from Zn, Al, Na, K, and Mg; B comprises one or more elements selected from Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, and Ti; C comprises one or more elements selected from B, S, Si, and N; D comprises one or more elements selected from S, F, Cl, and Br; m is selected from the range of 0.5 to 1.15, and can be selected from the range of 0.95 to 1.05; x is selected from the range of 0 to 0.1, and can be selected from the range of 0.001 to 0.005; y is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1; z is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.1; n is selected from the range of 0 to 0.5, and can be selected from the range of 0.001 to 0.

1.

8. A method for preparing a positive electrode active material, characterized in that: The following steps are involved: Providing lithium-containing phosphate precursors; grinding the lithium-containing phosphate precursor and a carbon source; The ground material is heated to a first temperature T1 at a first rate under a protective gas atmosphere and kept at the first temperature T1 for a first time t1, and then heated to a second temperature T2 at a second rate and kept at the second temperature T2 for a second time t2, to obtain a positive electrode active material. The positive electrode active material comprises a lithium-containing phosphate, and the X-ray diffraction spectrum of the positive electrode active material tested in a fully charged state satisfies: having a (311) crystal plane peak in the range of 35°-36°, having a (011) crystal plane peak in the range of 20°-21°, and the peak intensity I of the (311) crystal plane peak is 311 The peak intensity of the (011) crystal plane peak I 011 The ratio satisfies I 311 / I 011 ≥0.

008.

9. The preparation method according to claim 8, characterized in that: The first rate is less than or equal to 4°C / min, and can be optionally 1°C / min-4°C / min.

10. The preparation method according to any one of claims 8 to 9, characterized in that: The first temperature T1 is greater than or equal to 400°C, and may be 400°C-600°C, and may be 450°C-550°C.

11. The preparation method according to any one of claims 8 to 10, characterized in that: The first time t1 is greater than or equal to 1 hour, and can be optionally 1 hour to 7 hours, and can be further optionally 3 hours to 5 hours.

12. The preparation method according to any one of claims 8 to 11, characterized in that: The second temperature T2 is greater than or equal to 720°C, and can be optionally 720°C-850°C, and can be more optionally 750°C-810°C.

13. The preparation method according to any one of claims 8 to 12, characterized in that: The second rate is 1°C / min-10°C / min, and can be 5°C / min-9°C / min; and / or, The second time t2 is 5h-20h, and can be optionally 8h-15h.

14. The preparation method according to any one of claims 8 to 13, characterized in that: The carbon source comprises a first carbon source, the first carbon source comprises a water-soluble polymer, and optionally, the weight content of the first carbon source is ≥50%, optionally 50%-70%, based on the total weight of the carbon source.

15. The preparation method according to claim 14, characterized in that: The water-soluble polymer includes one or more of polyethylene glycol, polyaniline, and their respective derivatives.

16. The preparation method according to any one of claims 14-15, characterized in that: The carbon source also includes a second carbon source, and the second carbon source includes one or more of glucose, sucrose, lactose, and maltose, Optionally, the weight content of the second carbon source is ≤50%, optionally 30%-50%, based on the total weight of the carbon source.

17. A battery cell, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, characterized in that: The positive electrode film layer comprises the positive electrode active material according to any one of claims 1 to 7 or the positive electrode active material prepared by the preparation method according to any one of claims 8 to 16.

18. An electrical device, characterized in that: Comprising the battery cell according to claim 17.

Citation Information

Patent Citations

  • Fluorine and vanadium ion-doped lithium iron phosphate material and preparation method thereof

    CN102583300A

  • Lithium iron phosphate positive electrode active material, preparation method thereof and battery

    CN114068918A

Cited By

  • Lithium ion secondary battery, battery device, and power device

    CN120073043A

  • Lithium-ion secondary batteries, battery devices and electrical appliances

    CN120073043B